Crowdsourced - FREEMAN, Kenneth W. (Institutional Knowledge at Singapore Management University, 2015)
Kenneth W Freeman and Howard Thomas outline some of the crowdsourced ideas about the future of business schools and other institutions that emerged from the first Business Education Jam.